Spun biotextiles in tissue engineering and biomolecules delivery systems - Miranda, Catarina S. (2020)
Nowadays, tissue engineering is described as an interdisciplinary field that combines engineering principles and life sciences to generate implantable devices to repair, restore and/or improve functions of injured tissues. Such devices are designed to induce the interaction and integration of tissue and cells within the implantable matrices and are manufactured to meet the appropriate physical, mechanical and physiological local demands. Biodegradable constructs based on polymeric fibers are desirable for tissue engineering due to their large surface area, interconnectivity, open pore structure, and controlled mechanical strength. Additionally, biodegradable constructs are also very sought-out for biomolecule delivery systems with a target-directed action. In the present review, we explore the properties of some of the most common biodegradable polymers used in tissue engineering applications and biomolecule delivery systems and highlight their most important uses.